Blockade (motion picture) (leaflet) (1938)
018b-0055-001 BLOCKADE TERRIBLE EFFECTS ON CIVIL POPULATION INNOCENT WOMEN AND CHILDREN SUFFER GRAPHIC SCENES DEPICTED IN SPANISH CIVIL WAR FILM - THE STORY - Peace abides in the countryside in Spain. Luis tends his flocks and Marco tills the land. Norma, motoring to meet her father, crashes into their oxen cart and they rush to her assistance. Gallantly the two peasants escort her to the inn at Castelmare, and Norma and Marco, though from two different worlds, are attracted to each other. Basil, Norma's father, and his associate, Andre Gallinet, have been impatiently waiting Norma's arrival so that they may [ ] the following day for Granada, as their espionage in Castelmare has been successfully concluded. After her encounter on the road Norma is loath to leave, but her father insists. Next day, as the car carrying Norma, her father and Andre is speeding towards Granada, Marco and Luis are in their fields — when suddenly a noise like thunder, but out of a clear sky, rolls down their valley. It is the noise of guns. War, unexpected and terrible, has broken out over the land. Soon, in a rising tide of terror, peasants come fleeing before the oncoming army. But Marco is desperate at the thought of being driven from the land which is his life and he calls upon his countrymen to resist the challenge of the enemy and make a stand. So successful is the resistance thus organised that Marco is made a lieutenant and ordered to the important task of cleaning up spies operating in the district. In the course of this duty Marco shoots and kills Basil, not knowing he is Norma's father, and is then compelled to arrest her as an accomplice. Before she can be tried a sudden air-raid imprisons both captor and prisoner in a cellar. Death seems certain, but thanks to Luis they are rescued and Norma escapes. Re-captured, Norma is brought before General Vallejo. He tells her that owing to the intercession of Andre Gallinet on her behalf she will be given a military safe conduct. Norma is amazed to find that Andre is apparently betraying both sides; later that evening he makes it clear to her that he has no intention of letting her leave Spain, but that on the contrary she must work with him or face a firing squad. Her first mission is to carry an important code letter to Castelmare, which by now is in a state of blockade. Her message gives instructions for the torpedoing of a food-ship attempting to run into the harbour. On the way to Castelmare Norma again meets Marco, but he gives no sign of recognition. He speaks only a carefully worded warning, for he has been sent to watch her activities. Castelmare is a city of despair. The people are starving, air-raids have shattered their morale, the local defenders are losing hope. In a waterfront cafe Norma delivers her message through a waitress to Pietro, who has secret radio communication with the enemy. With two accomplices Pietro deciphers and sends on the instructions which will mean the destruction of the food-ship. It is not until Norma walks through the already half-ruined township that she realises the enormity of what she has done. She sees little children dying for the want of food, bereaved women sitting beside the remains of a school-house where not long ago their sons and daughters played — that was before the bombers came; she sees helpless people in the grip of a ruthless war machine, their one hope the arrival of the food-ship which she herself has already virtually sent to its doom. With the overwhelming horror that these sights bring, Norma rushes at once to Marco, confesses what she has done, and asks for his help. Not being able to trust her completely Marco arranges his own plan, aided by Luis. Distracted, Norma goes to Pietro and tells him that the orders have been changed. The submarine must not attack the food-ship, but return to its base at once and await further instructions. Pietro sends the message, but at this moment Marco, who has followed Norma, bursts in with his men and puts the spies under arrest. Pietro has enough time to dismantle the radio, and the submarine, receiving no confirmation, ignores the second message and proceeds on its original course. Soon after dawn the food ship appears over the horizon. All Castelmare throngs the waterfront. Women, children and old men watch the ship with joyful eyes. They are almost overcome with emotion and excitement as they see the vessel steaming towards the harbour from the open sea, bringing respite to the starvation they have borne. Inside the submarine terse orders are given. The torpedo is loaded and discharged. It is a direct hit. Slowly before the dull and hopeless eyes of the people of Castelmare the relief ship sinks. Norma is again questioned by General Vallejo, and in an agony of self-reproach she confesses her activites and incriminates Gallinet. When she has finished her story Gallinet himself appears, and Norma realises too late that even Vallejo is in the ring of traitors. As Gallinet suavely explains to Norma that he arranged to dispose of her father, and that now it is her turn, Marco rushes in to Vallejo with important news. The ship sunk by the torpedo was a decoy ship — an empty hull with no one on board, and now — THE REAL FOOD SHIP IS SAFELY COMING IN! Vallejo rushes to tell Gallinet, who begins at once to send off a message that will fetch the bombing planes. In desperation Norma shoots him; then with Marco she finds herself isolated at the mercy of Vallejo and his men. On the waterfront the populace have watched the food-ship with uncertain eyes. They do not understand. They saw one ship sunk only a short time before; they do not know what this second ship can be and they will not twice suffer the swift transition from joy to despair. Even when Luis comes ashore and excitedly tells his part in the night's work the strained silence persists. It is not until the ship begins to unload its precious cargo that an exultant cheer breaks from every throat. It is food at last! Food and medical supples ! The sick can be ministered to, the children will be fed! With the happy cries of the people ringing in their ears, Norma and Marco prepare for death - when suddenly Luis breaks in. He has brought the commandant of the army to face Vallejo in person. Vallejo is arrested. Complimenting Marco on his courageous effort for their cause the commandant suggests that he will try to arrange for a short term of leave for him so that with Norma he may find a little peace. That word "peace" springs a trigger in Marco's mind and the words come quickly, fed by the pent up thought and emotion of the past tragic days: "Peace! Where can you find it!" Our country has been turned into a battlefield. There'll no safety for old people and children . . . Women can't keep their families safe in their houses - they can't be safe in their own fields. Churches, schools and hospitals are targets . . . It's not war - war is between soldiers - it's murder. Murder of innocent people. There's no sense to it. The world can stop it - WHERE'S THE CONSCIENCE OF THE WORLD!" — THE CAST — Norma Madeleine Carroll Marco Henry Fonda Luis Leo Carrillo Andre Gallinet John Halliday Basil, Norma's father Vladimir Sokoloff General Vallejo Robert Warwick Commandant William Davidson Pietro Fred Kohler PRODUCED BY WALTER WANGER A FILM YOU MUST SEE! 292/946/18b/55